2013
DOI: 10.1016/j.apmr.2013.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Improvement and Resorption of Calcifications in Calcific Tendinitis of the Shoulder After Shock Wave Therapy at 6 Months' Follow-Up: A Systematic Review and Meta-Analysis

Abstract: We found a clinical improvement with a pooled total resorption ratio of 27.19 (95% confidence interval [CI], 7.20-102.67) and a pooled partial resorption ratio of 16.22 (95% CI, 3.33-79.01). SWT increases shoulder function, reduces pain, and is effective in dissolving calcifications. These results were maintained over the following 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 38 publications
5
55
0
1
Order By: Relevance
“…These findings are in line with the findings of Ioppolo et al [15] and Vavken et al [24]. Ioppolo et al [15] performed a meta-analysis on the clinical improvement and resorption of calcifications after shock wave therapy compared with sham treatment. Vavken et al [24] used a different cutoff point of 0.20 mJ/ mm 2 .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These findings are in line with the findings of Ioppolo et al [15] and Vavken et al [24]. Ioppolo et al [15] performed a meta-analysis on the clinical improvement and resorption of calcifications after shock wave therapy compared with sham treatment. Vavken et al [24] used a different cutoff point of 0.20 mJ/ mm 2 .…”
Section: Discussionsupporting
confidence: 86%
“…The exact mechanisms of action of the ESWT are largely unknown; Loew et al [17] postulated that the shock waves lead to a three-way mechanism of action: (1) mechanical effect resulting in deposit fragmentation; (2) molecular effect resulting in deposit phagocytosis; and (3) analgesic effect resulting in denervation of pain receptors. Shock wave therapy can be divided into three categories based on its energy levels: low-energy (\ 0.08 mJ/mm 2 ), middle-energy (0.08-0.28 mJ/mm 2 ), and high-energy ([ 0.28 mJ/mm 2 ) [1,15,20]. High-energy ESWT can induce fragmentation and destruction of solid bodies.…”
Section: Introductionmentioning
confidence: 99%
“…Five acceptable-quality reviews 36,38,47,49,50 and 1 high-quality review 35 addressed rotator cuff calcific tendinitis (RC-CT). The first SR included 20 individual studies (1544 participants).…”
Section: Rotator Cuff Calcific Tendinitismentioning
confidence: 99%
“…One review (6 studies included, 460 patients) evaluated the effectiveness of ESWT for functional improvement and reduction of pain in patients with calcific tendinitis of the shoulder. 50 Meta-analysis was performed in 4 of the 6 studies included for review because these had 2 treatment groups; the other 2 studies were analyzed descriptively because they had 3 treatment groups. This SR found that ESWT increases shoulder function, reduces pain, and is effective in dissolving calcifications.…”
Section: Rotator Cuff Calcific Tendinitismentioning
confidence: 99%
“…Extracorporeal shockwave therapy has emerged as an alternative therapy either when conservative treatment fails or when introduced prior to invasive procedures for rotator cuff disease, and its efficacy and low morbidity is well demonstrated [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%